(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article examines the role of Generation Z in Uzbekistan’s tourism and cultural heritage sector. It analyzes Gen Z’s characteristics as digital natives who prioritize authenticity, flexibility, work-life balance, and visual content. The author highlights the gap between traditional education and Gen Z’s needs, proposing practical reforms including digital technologies (VR/AR), dual education, storytelling, and digital marketing skills. The paper stresses that human creativity and emotional intelligence remain irreplaceable in tourism.